2005
DOI: 10.1007/s00438-005-0002-y
|View full text |Cite
|
Sign up to set email alerts
|

Alkaline pH-induced up-regulation of the afp gene encoding the antifungal protein (AFP) of Aspergillus giganteus is not mediated by the transcription factor PacC: possible involvement of calcineurin

Abstract: The afp gene encoding the antifungal protein (AFP) of Aspergillus giganteus has a prototypical alkaline gene expression pattern, which suggests that the gene might be under the control of the ambient pH-dependent zinc-finger transcription factor PacC. This notion is corroborated by the presence in the upstream region of afp of two putative PacC binding sites, afpP1 and afpP2, which are specifically recognised by the PacC protein of A. nidulans in vitro. However, in this report we provide several lines of evide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 43 publications
1
4
0
1
Order By: Relevance
“…To characterize the DNA-binding ability of GST-CrzA (amino acids 469-603), probes conforming to the S. cerevisiae Crz1p consensus-site CDRE [7] were synthesized ( Figure 7A). Two putative CDRE sites were identified in the A. nidulans chsB promoter, and five such sites were identified in the A. giganteus afp promoter, previously suggested to be under the control of the Ca 2+ -calcineurin signalling pathway [11]. CrzA binds to CDRE-1 from the chsB promoter and to CDRE-5 from the afp promoter ( Figures 7B and 7C), confirming that binding sequences for CrzA and Crz1p are very similar or identical.…”
Section: Crza and Slta Are Both Dna-binding Proteinssupporting
confidence: 74%
See 1 more Smart Citation
“…To characterize the DNA-binding ability of GST-CrzA (amino acids 469-603), probes conforming to the S. cerevisiae Crz1p consensus-site CDRE [7] were synthesized ( Figure 7A). Two putative CDRE sites were identified in the A. nidulans chsB promoter, and five such sites were identified in the A. giganteus afp promoter, previously suggested to be under the control of the Ca 2+ -calcineurin signalling pathway [11]. CrzA binds to CDRE-1 from the chsB promoter and to CDRE-5 from the afp promoter ( Figures 7B and 7C), confirming that binding sequences for CrzA and Crz1p are very similar or identical.…”
Section: Crza and Slta Are Both Dna-binding Proteinssupporting
confidence: 74%
“…The nuclear-localized zinc finger Crz1p transcription factor then activates the expression of genes whose promoters contain physiologically relevant CDREs (calcineurin-dependent response elements) [7] 5 -GNGGC(G/T)CA-3 , and up-regulates the expression of various target genes, including some which encode cation transporters that act at the plasma membrane or other membranous organelles [8][9][10]. We previously found that alkaline-pH-induced up-regulation of the Aspergillus giganteus afp (antifungal protein) gene can be prevented by FK506, an inhibitor of calcineurin [11]. To pursue afp regulation in the context of cation adaptation and homoeostasis, we have chosen to investigate Ca 2+ -mediated signalling in Aspergillus nidulans, an experimentally more amenable species than A. giganteus.…”
Section: Introductionmentioning
confidence: 99%
“…However, so far there are no data indicating that calcineurin-Crz1 can act in parallel to the Aspergillus PacC signaling pathway. Rather, it has been shown in Aspergillus giganteus that the alkaline pH-induced upregulation of the afp gene encoding an antifungal protein is mediated not by PacC but by calcineurin (87).…”
Section: Cross Talk With Other Signaling Pathwaysmentioning
confidence: 99%
“…In contrast, the function of antimicrobial proteins from prokaryotes and lower eukaryotes is less well studied. The benefit of the expression of antifungal proteins in ascomycetes, for example, could be an ecological advantage for the producing organisms in the competition for nutrients [23, 26], similarly to the function of fungal secondary metabolites as reported by [37]. This would imply the inducibility of the expression of antifungal proteins in the presence of microbial competitors or under unfavourable growth conditions.…”
Section: Introductionmentioning
confidence: 99%